PSYCHOLOGYCAL WELL-BEING ON EMERGING ADULTHOOD : THE INFLUENCE OF PARENTAL ATTACHMENT: indonesia - Fathyadiva, Syifa Andini; Safitri, Sasqia Desta (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
Emerging Adulthood is a transitional period experienced by adolescents. During this period, there are demands or developmental tasks that must be completed, such as the search for self-identity, fulfillment of the need for validation and emotional stability that affect how high or low psychological well-being. The purpose of this study was to determine whether parental attachment affects the level of psychological well-being of an adolescent entering the transitional period. There were 300 respondents in the study taken using an accidental sampling technique. The research data collection technique used a psychological well-being scale with a reliability of 0.904 and a parental attachment scale with a reliability of 0.885. The results showed a correlation coefficient (R) of 0.962 with a calculated F value of 3699.918 and a significance level of 0.001 (p <.001) meaning there is a significant relationship between Parental Attachment and Psychological Well-Being in Emerging Adulthood where the parental attachment variable provides an effective contribution of 92.5% to psychological well-being in emerging adulthood.